A Critical view to the concept of Unity of Existence in Quasi-Mystical School of Castaneda (based un “The Power of Silence”) - mohamad ebrahim malmir; fatemeh kolivand (مطالعات ادیان و عرفان تطبیقی, 2019)
Development of new moral and mystical schools is one of the consequences of modernity and human involvent in the age of iron  that human quest for worldly desires and enjoying of life is in the forefront of their teachings. Carlos Castaneda’s school, which is integrated with quasi-mystical belif and Indian mysticism, is a new school to be contemplated and criticized over issues like: forgetting the lord, negligance to resurection and the world hereafter, interest in magic, trending to hallucinogenic herbs, and etc. One of the outstanding subjects of discussion in the teachings of this school is thinking of unity (Unity of existence) with superior force of nature (intent, spirit, etc). Although, like other Castaneda’s teachings, this blief has somethings in common with pathenism thought of divine mysticism, particularly with Islamic mysticism, (such as pride avoidance, negligence to the world, etc) there are some issues to be discussed and criticized including: negligence to god – as a superior force – dominance on supperior force (intent, …), ease of attachment to god, failure to link death and survival, and … . Approaching to Castaneda’s school (based on “The Power of Silence”), the present atricle critically proposes the idea of unity of existence.